Paying Attention to Profitable Investments : Experimental Evidence from Renewable Energy Markets - Coville, Aidan; Orozco-Olvera, Victor; Reichert, Arndt (World Bank, Washington, DC, 2019)
This paper provides an explanation for why many information campaigns fail to affect decision-making. The authors experimentally show that a large information intervention about a profitable and climate-friendly household investment had limited effects if it only provided generic data. In contrast, it caused households to make new investments when it followed a campaign strategy designed to minimize information processing costs. This finding is consistent with a model of selective attention, where individuals prioritize information believed to be valuable after accounting for the costs of attending to the data that arise due to limited mental energy and time. The paper studies a range of possible mechanisms and finds corroborative evidence of selective attention as an inhibitor to learning.